2014
DOI: 10.1021/jm500687u
|View full text |Cite
|
Sign up to set email alerts
|

Studies Examining the Relationship between the Chemical Structure of Protoxin II and Its Activity on Voltage Gated Sodium Channels

Abstract: The aqueous solution structure of protoxin II (ProTx II) indicated that the toxin comprises a well-defined inhibitor cystine knot (ICK) backbone region and a flexible C-terminal tail region, similar to previously described NaSpTx III tarantula toxins. In the present study we sought to explore the structure-activity relationship of the two regions of the ProTx II molecule. As a first step, chimeric toxins of ProTx II and PaTx I were synthesized and their biological activities on Nav1.7 and Nav1.2 channels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 37 publications
3
60
0
Order By: Relevance
“…FLIPR studies (Fig. 7A) revealed that synthetic ProTx-II inhibits hNa V 1.7 in SH-SY5Y cells with an IC 50 of 0.40 Ϯ 0.07 nM, which is within the previously determined range (16,29,40). All ProTx-II analogues with mutations in Trp residues had reduced potency against hNav1.7 compared with ProTx-II.…”
Section: Lipidsupporting
confidence: 68%
See 1 more Smart Citation
“…FLIPR studies (Fig. 7A) revealed that synthetic ProTx-II inhibits hNa V 1.7 in SH-SY5Y cells with an IC 50 of 0.40 Ϯ 0.07 nM, which is within the previously determined range (16,29,40). All ProTx-II analogues with mutations in Trp residues had reduced potency against hNav1.7 compared with ProTx-II.…”
Section: Lipidsupporting
confidence: 68%
“…We were specifically interested in examining whether the hydrophobic patch might be important for membrane binding. Previous mutagenesis studies have shown that Trp residues affect the potency (39) and/or the selectivity (40) of ProTx-II as shown with analogues with the single mutations as follows: W5A, W7A, W24L, W30A (39), W30I, or amidated Trp-30 (40). In these earlier studies, the hydrophobic aromatic Trp residues were replaced with nonaromatic amino acid residues that possess a lower tendency to bind/insert into the membrane (41).…”
Section: Protx-ii Interaction With Model Lipidmentioning
confidence: 99%
“…Loss of function mutations on SCN9A, the gene encoding hNa V 1.7, result in unresponsiveness to pain, whereas gain of function mutations result in increased chronic and acute pain sensations [3,4]. Because of this link to pain, efforts to identify potent and selective inhibitors of hNa V 1.7 are underway [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were undertaken recently with the aim of improving potency, selectivity, stability, and bioavailability of venom-derived lead peptide compounds targeting Nav1.7 (19,(21)(22)(23).…”
Section: The Atomic Coordinates and Structure Factors (Code 5epm) Havmentioning
confidence: 99%
“…CcoTx1, like other site 4 microproteins (binding to S3-S4 linker of domain II) (36 -38), can be effectively dislodged from its binding site on the Nav1.7 channel by strong depolarization (23,44). In our studies, 5 nM D1Ia induced almost complete block of Nav1.7 current after a 20-min application; however, a subsequent positive depolarizing pulse to ϩ50 mV for 1 min has reversed the blocking effect of D1Ia by 83 Ϯ 10% (n ϭ 5) (supplemental Fig.…”
Section: Effects Of Post-translational Modification On Potency Andmentioning
confidence: 99%